The socio-political and medico legal and socio political practice of medicine in South Africa post 1994 - Carstens, Pieter Albert, 1960- (University of Pretoria, 2017)
Mini Dissertation (MPhil (Medical Law and Ethics))--University of Pretoria, 2016.